Entrepreneurial Intention Among Undergraduate Students Using The Entrepreneurial Intention Model - Wan Nawang, Wan Rasyidah (Indonesian Journal of Business and Entrepreneurship, 2023)
This study investigated undergraduate students’ entrepreneurial intentions using the Entrepreneurial Intention Model (EIM). The model was adapted from the Theory of Planned Behaviour (TPB). Three variables, namely professional attraction, social valuation, and entrepreneurial capacity were included in the study of entrepreneurial intention based on the EIM. This study applied a modified version of the Entrepreneurial Intention Question (EIQ) by Liñán and Chen. A convenience sample was drawn and a total of 136 students from Higher Education Institutions (HEIs) in Malaysia participated in the study. The questionnaire was distributed using Google forms through various social media applications such as WhatsApp, Twitter, and Facebook. The collected data was analysed using multiple linear regression analysis. Three hypotheses were generated in this study and the results showed that all three hypotheses were supported. Professional attraction, social valuation, and entrepreneurial capacity had an influence on university students' entrepreneurial intention. The results of this study showed that the students have a strong desire to become entrepreneurs and that they are interested in pursuing entrepreneurship as a career path in the future. Their social circles were also important to them, despite the fact that they were aware that entrepreneurship was not a high priority in their social circles. Apart from that, they are aware of the necessary skills, attitudes, and abilities to become entrepreneurs. This study is useful for higher learning institutions and governmental and non-governmental agencies to further enhance entrepreneurship development programs at the university level, particularly during the post-COVID-19 pandemic period. Keywords: entrepreneurial capacity, entrepreneurial intention, entrepreneurial intention model, professional attraction, social valuation